Characterization of Non-Type B Haemophilus influenzae Strains Isolated from Patients with Invasive Disease - Cerquetti, Marina (American Society for Microbiology, 2000)
Forty-one non-type b Haemophilus influenzae isolates from cases of invasive disease were characterized. By PCR capsular genotyping, 33 nonencapsulated strains, 4 type f isolates, and 4 b(−) strains were identified. By pulsed-field gel electrophoresis, the nonencapsulated isolates exhibited great genetic heterogenicity, whereas the type f and the b(−) strains seemed to have a clonal spread. Occurrence of the hifA gene was found by PCR in 18% of the nonencapsulated, 50% of the b(−), and all of the type f strains. Hemagglutinating fimbriae were generally expressed by nonencapsulated isolates when fimbrial gene hifA was present. Two nonencapsulated isolates not susceptible to ampicillin were detected; no strains were positive for β-lactamase production.